PRODUCTION AND LOCALISATION OF ALPHA-GRANULE PROTEINS IN MATURING MEGAKARYOCYTES: AN OVERVIEW ON ULTRA-STRUCTURAL ASPECTS OF MEGAKARYOCYTE MATURATION - Cramer, Elisabeth M; John, F; Vainchenker, William; Breton-Gorius, Janine (Thrombosis and Haemostasis, 1987)
In order to study the production of α- granule proteins in maturing megakaryocytes, we used immunocytochemical techniques performed on cultured and enriched bone marrow megakaryocytes. Cultures were prepared from bone marrow CFU-MK with the methylcellulose and plasma clot techniques. Preparation of bone marrow megakaryocytes was carried out from human or pig rib marrow separated on percoll gradient and counterflow centrifugation. Megakaryocyte preparations were 90$ pure and represented 85$ of those in the whole marrow. Activation was prevented with prostacyclin and prefixation with low concentration glutaraldehyde. A panel of monoclonal and polyclonal antibodies, against different platelet membrane glycoproteins and against cytoplasmic antigens (such as von Willebrand Factor (vWF), fibrinogen (Fg) and thrombospondin (TSP)) was used and observed by immunofluorescence or by immunogold in electron microscopy.The first megakaryocytic precursors, promegakaryoblasts (PMKB) identifiable by these antibodies were found at day 5 of culture. They had the size of lymphocytes, were labelled for GP lib, Ilia, and Ilb-IIIa complex but not for GPIb which appeared later. Platelet peroxidase was also present, otherwise these cells were devoid of α- granules and only a few of them exhibited a diffuse pattern for vWF immunolabelling. One day later membrane GPIb and diffuse cytoplasmic labelling for vWF were detected in the majority of PMKB. At day 9 of culture, this pattern of labelling for vWF became more intense and granular. The same pattern was observed for TSP and platelet factor 4. Immunoelectron microscopy showed that in immature megakaryocytes isolated from human bone marrow, labelling for vWF and TSP was observed in vesicles located in the Golgi region; in addition numerous small granules less than 0.1pm in diameter, round or elongated in shape, were labelled for these antigens. In mature human megakaryocytes, the labelling for these cytoplasmic antigens was restricted to the platelet α- granules in a distribution pattern similar to that of platelet α- granules. However, the labelling for Fg was consistently less intense in the granules of immature and mature megakaryocytes than in platelets.Because in platelets α- granule immunolabelling for vWF is associated with tubular structures which are specially prominent in porcine species, we studied vWF and tubular structures in pig megakaryocytes. Standard and immunoelectron microscopy revealed the simultaneous appearance of both in the small vesicles located in the Golgi area in the small immature α- granules and later in the mature α- granules. In mature megakaryocytes, labelling for vWF was intense and restricted to the α- granules. It was distributed eccentrically as in porcine blood platelets. Gold particles were often eccentrically located at one pole of the α- granule either labelling only its periphery or outlining one side of an elongated granule. Standard electron microscopy showed that tubular structures were very numerous in the mature α-granules, regularly spaced, arranged in parallel and usually located at one side of the granule. On the other hand platelets from pigs with homozygous von Willebrand disease were found to be completely devoid of both tubular structures and immunolabelling for vWF suggesting that the tubules represent the vWF itself.In acute megakaryoblastic leukemia, several phenotypes of PMKB were found in different patients, which corresponded to the stages of maturation of cultured megakaryocytes from CFU-MK.In conclusion, immunolabelling methods combined with megakaryocyte enrichment techniques are useful tools to study the origin of megakaryocyte (and platelet) granular proteins.